"Don't you know I own the road?" The link between narcissism and aggressive driving. (January 2018) - Bushman, Brad J.; Steffgen, Georges; Kerwin, Thomas; Whitlock, Tyler; Weisenberger, Janet M.
Highlights: Aggressive driving is the leading cause of traffic fatalities. Narcissists have inflated self-views and low empathy for others. Due to their sense of entitlement, narcissists might think they "own the road". In 3 studies, we found a positive relation between narcissism and aggressive driving. Abstract: Aggressive drivers can make driving dangerous. Over 50% of traffic fatalities are caused by aggressive driving. This research tests whether narcissists are more aggressive drivers than other individuals. Narcissists think they are special people who deserve special treatment. When they don't get the special treatment they think they deserve, narcissists often lash out at others in an aggressive manner. Narcissists might think they "own the road" and can drive anyway they want, and that other drivers should get out of their way. In the article, we conduct three studies to test the link between narcissism and aggressive driving. In Studies 1 ( N  = 139) and 2 ( N  = 100), Luxembourgish motorists completed a measure of narcissism and a self-report measure of aggressive driving. In Study 3 ( N  = 60), American university students completed a measure of narcissism and then completed a driving simulation scenario that contained a number of frustrating elements. Several measures of aggressive driving and road rage were obtained. In all three studies, narcissism was positively related to aggressive driving. A meta-analysis found an average correlation of r  = 0.35 across the three studies. This research replicates previous research linking narcissism to aggression, and extends it to a driving context.